2019
DOI: 10.29252/jafm.12.04.29455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Al2O3/Water Nanofluid on Natural Convection Heat Transfer of Corrugated ┐ Shaped Cavity: Study the Different Aspect Ratio of Grooves

Abstract: In this paper, the effect of γ-Al2O3/water nanofluid on the flow pattern and natural convection heat transfer of corrugated ⅂ shaped cavity is investigated numerically by the Lattice Boltzmann Method (LBM). The effects of nanoparticles solid volume fraction (ϕ=0-0.006), Rayleigh number (Ra=10 3-10 6) and the aspect ratio of grooves cavity (h/H=0.05-0.15) on the streamlines, isotherms and averaged Nusselt number have been examined. In addition, a comparison between γ-Al2O3/water nanofluid and MWCNT-Fe3O4/Water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Higher nanoparticle concentrations were reported to increase the heat transfer coefficient [18,19] as well as the thermal conductivity [20] but decreases the specific heat capacity [21]. On the contrary, in the study by Pandey et al [22] of Al2O3/water nanofluid in a plate heat exchanger, it was found that the heat transfer behaviour improved with a decrease in the nanoparticle concentration.…”
Section: Introductionmentioning
confidence: 93%
“…Higher nanoparticle concentrations were reported to increase the heat transfer coefficient [18,19] as well as the thermal conductivity [20] but decreases the specific heat capacity [21]. On the contrary, in the study by Pandey et al [22] of Al2O3/water nanofluid in a plate heat exchanger, it was found that the heat transfer behaviour improved with a decrease in the nanoparticle concentration.…”
Section: Introductionmentioning
confidence: 93%
“…To improve the working fluid' s thermal conductivity, nanoparticles have been introduced to the base fluid by numerous writers. [1][2][3][4][5]. Other scientists looked at hybrid nanofluids and their impact on heat transmission [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Mohebbi et al [9] studied the effect of γ-Al2O3 nanoparticle addition in water base fluid on the natural convection heat transfer of corrugated ⅂ shaped cavity. They have employed the Lattice Boltzmann Method for their study.…”
Section: Introductionmentioning
confidence: 99%